The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1590/s0102-311x1997000300013
|View full text |Cite
|
Sign up to set email alerts
|

Validación de "infarto de miocardio" como causa de muerte en certificados de defunción, Barquisimeto, Estado Lara, Venezuela

Abstract: Death rates due to Ischemic Heart Disease (IHD) are widely used to assess regional and national cardiovascular health status. However, their validity is questionable, essentially because they are based on death certificates (DCs). The present study was conducted in the Greater Metropolitan Area of Barquisimeto (Lara State, Venezuela), from June 1991 to July 1992. The purpose was to establish the validity of the diagnosis of myocardial infarction in DCs of intrahospital deaths. Efforts were made to locate all c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…A study in Venezuela, for example, found that about one-third of the death certificates listing myocardial infarction as a cause of death were in error according to WHO MONICA case definitions 48. Because questionnaires are so important in collecting health information, a catalogue of biases in questionnaires is now available 49…”
Section: Resultsmentioning
confidence: 99%
“…A study in Venezuela, for example, found that about one-third of the death certificates listing myocardial infarction as a cause of death were in error according to WHO MONICA case definitions 48. Because questionnaires are so important in collecting health information, a catalogue of biases in questionnaires is now available 49…”
Section: Resultsmentioning
confidence: 99%